X - Belmore, Rebecca (InTensions, 2012)
I remember the long hot summer of 1990. Twenty years since Oka. I easily recall images of the Canadian military surrounding the Mohawk nation. This moment in our history affirmed what I have known since childhood. I was born in a colonial space. I am aware that our land and Aboriginal rights are constantly being eroded. We must continually fight to hang onto what we have left. Using my intellectual and physical abilities I create images that mark our experience, mapping our space in time. This is how I view my role as an artist amongst our people. I imagine this is the way it has always been. X, responds to Oka in the immediacy of the present space of Price Choppers in Peterborough. They are having a ceremony across the street to rebury a two thousand year old Aboriginal man, found when they created the parking lot. What strikes me about the reburial site is that it is such a generic setting - between a parking lot and a sidewalk on a very busy street - no trees, no meandering sidewalk, no benches, absolutely outside of public spaces created out of civic pride. The repetitive actions of marking, erasing, marking and erasing large X’s – two Aboriginal women, contemporary individuals, with specific identities are going about our work in current time and space. And yes, across the street, a ritual of return, a reburial of what was disturbed and removed is taking place. The ancient ones obviously used this site in a very different way. Us –with our vehicles, parking lots, grocery stores, telephones and cars. The sacred fire for the reburial, the spiritual return quietly takes place while contemporary life moves on. I guess on some level, I am seeing us as them and them as us. How long before Price Chopper and the parking lot become something else?